Influence factors for using hydraulic binders for soil stabilisation of fine-grained soils in cold environment. Issue 1 (April 2021) - Rothhämel, Mirja; Al-Jabban, Wathiq Jasim; Laue, Jan
Abstract: The stabilization of soft soils with hydraulic binder is a common technique all over the world. By means of stabilization the engineering properties of fine-grained soils can be improved, where settlements or stability problems have to be handled. Lime and cement are usual binders. The use of industrial by-products as binders has been investigated and some are already established on the market in combination with cement, as e.g. fly ash or slag. Nowadays the reduction of CO2 is in focus, leading to a search for more by-products from the industry that are suitable to use as hydraulic binder. One of these is cement kiln dust (CKD) that is started to be used commercially as a binder in combination with cement. Fine-grained soils are often frost susceptible i. e. they show frost heave and/or thaw weakening. These typical problems are handled by improvement with hydraulic binder in countries with moderate climate [33]. In countries with cold climate, near surface soil stabilization with hydraulic binder is less used. One reason for this reduced usage are uncertainties about the influence of low temperature on the expected stabilizing effects of the hydraulic binder. Previous research has shown that the strength of the stabilized material is decreased by frost impact, when compared to without frost. New research results have shown a recovering of the strength after a reduction due to frost [1; 2]. In the present contribution, a multiple linear regression analysis is presented for identifying significant influencing factors for soil stabilization of fine-grained subgrade with hydraulic binders in cold environment. The regression analysis is based on the results from three earlier published laboratory studies [3-5], where the unconfined compressive strength (UCS) was used as a measure of strength. The laboratory studies involved different soil types, different binders (mainly by-products), and varying binder contents. The results from the laboratory studies show that the strength increases during curing in cold environment. After twelve freeze-thaw-cycles the strength is reduced for several samples, compared to without freeze-thaw-cycles, but it is higher than without stabilization. A recovering of strength after a subsequent curing time after the freeze-thaw-cycles is visible in some cases for the stabilized samples. The multiple linear regression analysis presented here shows the influence of the binder content, as well as the freeze-thaw-cycles and the curing time, on the strength.